ANALISIS TATA KELOLA PEMERINTAHAN PADA BIDANG KEUANGAN DI PROVINSI RIAU - Dody, Dody Rahmadi (JURNAL KEBIJAKAN PUBLIK, 2024)
Good governance in the field of regional finance is one of the important factors in realizing sustainable development and community welfare. As part of the local government system, efficient, transparent, and accountable financial management. This research is important to resolve the challenges of regional financial governance to support development in Riau Province.  This research uses the library research method by making good literature from books, journals and scientific articles. The result of this research is that good financial governance in Riau Province is very crucial to support sustainable development and community welfare. Although Riau has great potential in the financial sector, especially from natural resources, challenges such as dependence on the oil and gas sector, suboptimal asset management, and potential budget misuse still hinder progress. Therefore, efficient, transparent, and accountable regional financial management is needed to improve public services and accelerate development. Local governments need to improve budget planning, increase the capacity of the apparatus, and diversify sources of revenue. The use of information technology and strengthening supervision are also needed to prevent budget abuse. With these measures, Riau Province has the opportunity to achieve financial independence and more equitable development, which will ultimately improve people's welfare.